Effectiveness of lenalidomide in relapsed primary cutaneous diffuse large B‐cell lymphoma, leg type. Issue 5 (5th April 2019) - Al Dhafiri, Mahdi; Sicre de Fontbrune, Flore; Marinho, Eduardo; Deschamps, Lydia; Di‐Lucca, Julie; Crickx, Beatrice; Descamps, Vincent
Key Clinical Message: The primary cutaneous diffuse large B‐cell lymphoma, leg type (PCDLBCL‐LT) has a poor prognosis. R‐CHOP with or without radiotherapy is the available recommendations for first‐line treatment. Relapses/refractory cases are frequent with no standardized therapeutic guidelines. Lenalidomide seems to be an excellent therapeutic option as a second‐line treatment of relapsed PCDLBCL‐LT. Abstract : The primary cutaneous diffuse large B‐cell lymphoma, leg type (PCDLBCL‐LT) has a poor prognosis. R‐CHOP with or without radiotherapy is the available recommendations for first‐line treatment. Relapses/refractory cases are frequent with no standardized therapeutic guidelines. Lenalidomide seems to be an excellent therapeutic option as a second‐line treatment of relapsed PCDLBCL‐LT.